Relationship between Vitamin D status and the vaginal microbiome during pregnancy - Jefferson, Kimberly K. (J Perinatol, 2019)
OBJECTIVE: Evidence supports an inverse association between vitamin D and bacterial vaginosis (BV) during pregnancy. Furthermore, both the vaginal microbiome and vitamin D status correlate with pregnancy outcome. Women of African ancestry are more likely to experience BV, to be vitamin D deficient, and to have certain pregnancy complications. We investigated the association between vitamin D status and the vaginal microbiome. STUDY DESIGN: Subjects were assigned to a treatment (4 400 IU), or a control group (400 IU vitamin D daily), sampled 3 times during pregnancy, and vaginal 16S rRNA profiles and plasma 25-hydroxyvitamin D [25(OH)D] concentrations were examined. RESULT: Gestational age and ethnicity were significantly associated with the microbiome. Megasphaera correlated negatively (p = 0.0187) with 25(OH)D among women of African ancestry. Among controls, women of European ancestry exhibited a positive correlation between plasma 25(OH)D and L. crispatus abundance. CONCLUSION: Certain vaginal bacteria are associated with plasma 25(OH)D concentration.